LEFT ATRIAL DYSFUNCTION BY SPECKLE TRACKING ECHOCARDIOGRAPHY IN YOUNG SUBJECTS WITH HIV INFECTION - Mirea, Oana; Donoiu, Ionut; Manescu, Mirela; Dumitrescu, Florentina; Istratoaie, Octavian; Militaru, Constantin (Ultrasound in medicine & biology, 2022)
Despite effective antiviral treatment, the rate of acute cardiac events remains high in subjects with HIV. Left atrium strain (LAS) was shown to be an independent predictor of cardiovascular events in the general population. Therefore, the aim of this study was to investigate whether left atrial (LA) strain has incremental value over conventional echocardiographic parameters to identify HIV subjects with subclinical cardiac disease. We prospectively included 100 young patients (mean age 31.3±4.8; 60 males) with acquired HIV (mean interval from diagnosis 18 ± 9 years) and 80 healthy volunteers matched by age and gender. Echocardiography was performed using a Vivid iQ machine (GE Healthcare). Left ventricular (LV) and LA conventional measurements were obtained according to current recommendations. LA strain during the reservoir (LASr) phase was calculated using a dedicated tracking tool (EchoPac v 20.4). The treatment protocol included reverse-transcriptase inhibitors (RTIs) (40%), a combination of RTIs with non-nucleoside reverse transcriptase inhibitors (NNRTIs) (25%), a combination of RTIs with HIV protease inhibitors (20%), or a combination of RTIs with HIV integrase inhibitors (15%). No significant difference in LV ejection fraction between the groups was found (57±6 vs. 59±7, p=0.15). Subjects with HIV had higher LV mass (78±19 vs. 68±15, p< 0.001) and E/Eˈ ratio (6±2 vs. 5±1, p< 0.01). While LA volume showed similar values (38 ±11ml vs 41 ±12 ml, p=0.14), LASr was significantly reduced in patients with HIV compared to healthy subjects (33±8 vs. 38±7, p < 0.001). In multivariate analysis, LASr was independently associated with age (p=0.01) and years since HIV diagnosis (p=0.03). The choice of treatment protocol did not influence LA strain (p=0.16). In our study, both groups had similar LA volumes according to measurements derived from conventional echocardiography, while 2D-STE measurements proved a significantly reduced LA strain during the reservoir phase in patients with HIV compared to healthy volunteers. Our study shows evidence that LA strain is impaired in young asymptomatic subjects with HIV, prior to conventional echocardiographic measurements and the measurement could be useful in the detection of subjects at risk for developing heart failure.